(untitled) (Journal of Comparative Social Work, 2009)
Is it possible to gain a fuller understanding of social work by using the concept of discourse? In this article I examine social work as a discursive practice. My aim here is to discover whether this kind of discursive framing may add to our understanding of the discipline of social work. Discourse11, as I understand it, is a social phenomenon based upon a social and a cultural relationship serving as a foundation for making shared assessments (Magnusson 1998, Fook, 2002). As used here, discourse refers to a more extensive social phenomenon both formed and spread by language and which involves the contributions of many people through time (Magnusson, 1998:182). When this is related to a discipline such as social work, discourse also involves issues involving competency as linked to a position or status.